The disputes in the construction of the National Curricular Common Base: notes on the content of educational policy (Olhar de Professor, 2023)
The article aims to understand the disputes that occurred in the construction of the National Common Curricular Base (BNCC), more specifically, around the content of the policy and educational proposal within the Ministry of Education and the National Council of Education, during a certain period of time. historical, political and social period in which changes in education are part of a larger movement, whose totality and historicity need to be understood from the capital crisis in its different neoliberal stages that redefine the State and bring implications in educational policies. We try to show the correlation of forces in the construction process of the BNCC in the National Council of Education and in the Ministry of Education that resulted in the enactment of the current BNCC. The research is characterized as qualitative; in the methodological path, we used the approach of influence and text production of the policy cycle. At the end of the article, we show that the construction process of the BNCC consisted of permanent debates on public education as a right.
Keywords: Educational Policy. BNCC. Public-private.